2003
DOI: 10.1002/hipo.10133
|View full text |Cite
|
Sign up to set email alerts
|

Expression of plasma membrane GABA transporters but not of the vesicular GABA transporter in dentate granule cells after kainic acid seizures

Abstract: Kainic acid-induced seizures cause a marked increase in the expression of glutamate decarboxylase 67 (GAD67) in granule cells of the dentate gyrus. To determine the possible modes of sequestration of newly formed gamma-aminobutyric acid (GABA), we used in situ hybridization and immunocytochemistry to investigate the expression of several proteins related to GABA in dentate granule cells of rats 4 h to 60 days after kainic acid-induced status epilepticus and in controls. GAD67 and GAD65 mRNA levels were increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
47
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 53 publications
7
47
4
Order By: Relevance
“…In contrast, it has also been reported that VGAT mRNA is not expressed in normal adult rats and even after kainite-induced seizures (Chaudhry et al, 1998;Sperk et al, 2003). Against this discrepancy, our in situ hybridization detected very faint signals for VGAT mRNA in the granule cell layer in some, but not all, sections.…”
contrasting
confidence: 76%
“…In contrast, it has also been reported that VGAT mRNA is not expressed in normal adult rats and even after kainite-induced seizures (Chaudhry et al, 1998;Sperk et al, 2003). Against this discrepancy, our in situ hybridization detected very faint signals for VGAT mRNA in the granule cell layer in some, but not all, sections.…”
contrasting
confidence: 76%
“…However, one difference is that we found relatively high expression of IRVGAT in terminals, as well as high VGAT mRNA (data not shown) in cell bodies of dual-phenotype GABA/glutamate neurons in AVPV neurons. In contrast, IRVGAT is undetectable (Chaudhry et al, 1998;Sperk et al, 2003) in granule cells, and VGAT mRNA is present only at low levels in adults (Lamas et al, 2001). Regardless of these differences, work from granule cells and our present findings from AVPV neurons provide compelling evidence that dual-phenotype GABA/glutamate neurons are not artifacts, but rather serve important physiological functions.…”
Section: Discussionmentioning
confidence: 45%
“…Thus, the moderate strength of VGAT immunoreactivity in glutamatergic terminals possibly underestimates to some degree the relative amount of VGAT occurring in these terminals. To further support the specificity of the VGAT immunoreaction, and because several groups have failed to find VGAT immunoreactivity in the hippocampal mossy fiber terminals (Chaudhry et al, 1998;Sperk et al, 2003), we tested a variety of VGAT antibodies raised in different species and directed against 2 examples are shown) showed a low expression of VGAT in addition to VGLUT1 (arrowheads). B, For comparison, interneurons isolated from the dentate gyrus and the hilar region were identified electrophysiologically.…”
Section: Electron Microscopic Evidence For Vgat In Glutamatergic Mossmentioning
confidence: 99%